One For All and All For One: Intra-Organizational Dynamics in Humanitarian Action - Webster, Mackinnon (Tufts Archival Research Center, 2005)
Submitted in partial fulfillment of the degree of Master of Arts in Law and Diplomacy at the Fletcher School of Law and Diplomacy. Published through the Feinstein International Center. Abstract: A significant proportion of humanitarian assistance is now delivered by NGOs which have in effect become federated transnational organizations--alliances of members from different countries--all seeking to provide assistance in times of crisis. This report describes research carried out to better understand how these transnational bodies organize their membership, deliver, and accountability systems in times of crisis. This report is the result of a study commissioned by Oxfam America. We examined the field response systems and structures of six NGOs to understand how they function during emergencies. A description of the organizations is included in the report. We identify six key learning points that are important for multi-member organizations operating in emergency contexts.